Ethanol Inhibits Aflatoxin B1 Biosynthesis in Aspergillus flavus by Up-Regulating Oxidative Stress-Related Genes - Ren, Yaoyao; Jin, Jing; Zheng, Mumin; Yang, Qingli; Xing, Fuguo (Frontiers in Microbiology, 2020)
As the most carcinogenic, toxic and economically costly mycotoxins, aflatoxin B1 (AFB1) is primarily biosynthesized by Aspergillus flavus and A. parasiticus. Aflatoxin biosynthesis is related to oxidative stress and functions as a second line of defense from excessive reactive oxygen species. Here, we find that ethanol can inhibit fungal growth and AFB1 production by A. flavus in a dose-dependent manner. Then, the ethanol’s molecular mechanism of action on AFB1 biosynthesis was revealed using a comparative transcriptomic analysis. RNA-Seq data indicated that all the genes except for aflC in the aflatoxin gene cluster were down-regulated by 3.5% ethanol. The drastic repression of aflatoxin structural genes including the complete inhibition of aflK and aflLa may be correlated with the down-regulation of the transcription regulator genes aflR and aflS in the cluster. This may be due to the repression of several global regulator genes and the subsequent over-expression of some oxidative stress-related genes. The suppression of several key aflatoxin genes including aflR, aflD, aflM and aflP may also be associated with the decreased expression of the global regulator gene veA. In particular, ethanol exposure caused the decreased expression of stress response transcription factor srrA and the over-expression of bZIP transcription factor ap-1, C2H2 transcription factors msnA and mtfA, together with the enhanced levels of anti-oxidant enzymatic genes including Cat, Cat1, Cat2, CatA and Cu, Zn superoxide dismutase gene sod1. Taken together, these RNA-Seq data strongly suggest that ethanol inhibits AFB1 biosynthesis by A. flavus via enhancing fungal oxidative stress response. In conclusion, this study served to reveal the anti-aflatoxigenic mechanisms of ethanol in A. flavus and to provide solid evidence for its use in controlling AFB1 contamination..